Optimization of soft templated mesoporous carbon synthesis using Definitive Screening Design - Libbrecht, Wannes; Deruyck, Frank; Poelman, Hilde; Verberckmoes, An; Thybaut, Joris; De Clercq, Jeriffa; Van Der Voort, Pascal (Chemical engineering journal (Lausanne, Switzerland : 1996), 2015)
[Display omitted] •Ratio precursor to surfactant is most significant parameter for mesopore formation.•Optimal mesoporous carbon has a surface area of 712m2/g and pore volume of 0.78cm3/g.•BPA adsorption is mainly influenced by mesoporous surface area and carbon content. The synthesis of soft template mesoporous carbons was optimized with a Definitive Screening Design (DSD), a recently developed design of experiments (DOE) method. Such a design enables to investigate the effect of synthesis parameters including their interactions or quadratic effects, on the material properties. The mesopore formation was influenced mostly by the ratio precursor/surfactant, other significant effects were curing time and carbonization temperature. The micropore formation was significantly influenced by the curing time and the carbonization temperature. The DSD was used to optimize the mesoporous surface area which could improve its potential as adsorbent. Via a validation experiment, a material with optimal mesoporous surface area (393m2/g) was synthesized, showing a total surface area of 712m2/g and a large pore volume of 0.78cm3/g. The different mesoporous carbons, synthesized according to the DSD, were tested for the adsorption of bisphenol A (BPA). This allowed to investigate the effect of material properties on the adsorption capacity, which varied between 12 and 163mg/g. Via regression analysis, the mesoporous surface area and the carbon content of the mesoporous carbons were identified as the main factors influencing the adsorption of BPA.